BET 2: negative B natriuretic peptide testing confirms low risk stratification for patients with a definite pulmonary embolus. Issue 6 (19th May 2015) - Ferguson, Craig; Horner, Daniel
Abstract : A shortcut review was carried out to establish whether a negative B natriuretic peptide could identify patients with confirmed pulmonary embolus at low risk for a complicated clinical course and therefore potentially suitable for outpatient therapy. Two systematic review/meta-analyses were found directly relevant to the three-part question. A further six prospective cohort studies of high quality postdating the systematic review were also found, relevant to the three-part question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that in normotensive patients with confirmed pulmonary embolism, a negative B natriuretic peptide or NTProBNP confers a low clinical risk of complications. When used in addition to a clinical risk scoring system such as the simplified pulmonary severity index, the risk becomes negligible (<1%). Such patients could be considered for outpatient therapy direct from the emergency department.